The sun is also a star [videorecording (DVD)] - Shahidi, Yara; Melton, Charles, 1991-; Leguizamo, John (Warner Bros. Home Entertainment, 2019)
College-bound romantic Daniel Bae and Jamaica-born pragmatist Natasha Kingsley meet, and fall for each other, over one magical day amidst the fervor and flurry of New York City. Sparks immediately fly between these two strangers, who might never have met had fate not given them a little push. But will fate be enough to take these teens from star-crossed to lucky in love?